خصوصية الوساطة في المنازعات الإدارية (Comprehensive Journal of Science, 2025)
Mediation is a modern technique for facilitating negotiations between conflicting parties. It is performed by a neutral third party called the mediator. The mediator's work, which ranges from negotiating through mediation sessions and meetings with the parties, to bringing their viewpoints closer together on proposed solutions, aims to reach a settlement agreement and resolve the conflict. This requires specific skills and qualifications from the mediator, which provides additional safeguards during the mediation process, instills trust between the parties, and encourages mutual cooperation to resolve the issues related to the conflict. This is especially true since the mediator always seeks to calm tense relations between the conflicting parties and preserve their future relationships. The mediation process and its procedures are not in themselves an end sought by the parties to the conflict, but rather merely a means for them to end the conflict. This does not preclude the possibility that the mediation process will end without achieving its intended goal and objective. However, if the parties’ objective is achieved and they agree to settle the dispute, the primary objective of resorting to mediation is achieved, and the mediation process ends with the signing of a settlement agreement between the parties, and we move to the stage of implementing the agreement.
Keywords: Mediation, Administrative Disputes, Mediator, Mediation Procedures, Negotiations